Negotiating Cyprus: The Missing Dimension - ÖZYURT, NİYAZİ ONUR (İstanbul Kültür Üniversitesi, 2022)
The Cyprus Problem started as an ethnic conflict within a small circle and reached international dimensions by enlarging its circle. Greek Cypriots and Turkish Cypriots are the founding duos and the two most populous communities on the island. Although historically the starting point differs according to the parties, the problem in Cyprus started to be shaped since the mid-1950s. This problem resulted in a Republic with the 1960 international treaties, the Republic of Cyprus. Only, the Republic of Cyprus did not last longevity. The Republic of Cyprus continued, but the rights of Turkish Cypriots remained on paper. The events of late 1963 and 1964 marked the beginning of insecurities at the far end between the parties to be experienced in the future. The Cyprus Negotiations is the general name of the numerous talks held for a solution. Discussion of the federal state system for the solution has been ongoing since the mid-1960s. However, the rapprochements experienced in the name of a solution served a purpose, except for a solution. The Cyprus negotiations have become a conundrum due to the different interpretations of the federal partnership by the parties. Consequently, it is apparent that the Federation proposal has been blocked and has been no concrete result achieved for years. In Cyprus problem, where alternative solutions may be discussed, proposals other than the Federation deserve serious consideration.
Kıbrıs'ı Müzakere Etmek: Eksik Boyut
▪ Yüksek lisans tezi.
Keywords: Cyprus Problem; Cyprus Negotiations; Annan Plan